2013
DOI: 10.1371/journal.pone.0053850
|View full text |Cite
|
Sign up to set email alerts
|

Germline DNA Copy Number Aberrations Identified as Potential Prognostic Factors for Breast Cancer Recurrence

Abstract: Breast cancer recurrence (BCR) is a common treatment outcome despite curative-intent primary treatment of non-metastatic breast cancer. Currently used prognostic and predictive factors utilize tumor-based markers, and are not optimal determinants of risk of BCR. Germline-based copy number aberrations (CNAs) have not been evaluated as determinants of predisposition to experience BCR. In this study, we accessed germline DNA from 369 female breast cancer subjects who received curative-intent primary treatment fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Germline DNA was extracted from peripheral blood samples of both cases and controls, using commercially available Qiagen TM (Mississauga, Ont., Canada) DNA isolation kits, as described earlier [Sehrawat et al, 2011;Sapkota et al, 2013a]. Whole genome genotyping was carried out using the Affymetrix Genome-Wide Human SNP Array 6.0, following the guidelines provided by the manufacturer.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Germline DNA was extracted from peripheral blood samples of both cases and controls, using commercially available Qiagen TM (Mississauga, Ont., Canada) DNA isolation kits, as described earlier [Sehrawat et al, 2011;Sapkota et al, 2013a]. Whole genome genotyping was carried out using the Affymetrix Genome-Wide Human SNP Array 6.0, following the guidelines provided by the manufacturer.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Further, we have demonstrated that copy-neutral losses of heterozygosity are also an important class of structural variations and serve as biomarkers of prognostic value in a BC setting [Sapkota et al, 2013a]. Large CNVs have an appreciable impact on many human diseases, including non-small-cell lung cancer, HIV infection, developmental delay, schizophrenia, autism, and idiopathic learning disability [Glessner et al, , 2010Hollox and Hoh, 2014;Li et al, 2014].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…With the advent of SNP genotyping platforms that can measure both CNVs and CN-LOHs, it is now possible to investigate potential roles of these large chromosomal defects as genetic determinants for complex diseases using germline DNA. A recent study conducted by us that aimed to evaluate the role of germline CNVs and CN-LOHs in breast cancer recurrence identified multiple copy number aberrations (2 copy number gains and 5 CN-LOHs) showing statistically significant differences between recurrence-free survival probabilities with and without these aberrations [Sapkota et al, 2013a]. Of these, 3 CNLOHs were successfully validated by qPCR.…”
Section: Cnvsmentioning
confidence: 99%
“…As an alternative source of genetic heritability for breast cancer, structural variations such as copy number variations (CNVs) and copy-neutral loss of heterozygosity (CN-LOH) are being interrogated for their associations with breast cancer predisposition as well as for disease recurrence [Wellcome Trust Case Control Consortium, 2010;Sapkota et al, 2013a]. GWAS literature has also witnessed few reports providing evidence for genetic interactions as another source to explain the remaining genetic risk of breast cancer [Milne et al, 2010;Campa et al, 2011;Nickels et al, 2013;Sapkota et al, 2013b].…”
mentioning
confidence: 99%